SOSIALIASI QUISIHING DALAM MENJAGA KEAMANAN DATA PRIBADI DI PONDOK PESANTREN NAFIDATUNNAJAH - Andrian Hidayat; Ade Napila (Abdi Jurnal Publikasi, 2025)
The use of increasingly advanced information technology has made various parties feel various advantages as well as challenges for its users. From the various benefits or conveniences obtained, there are usually loopholes that can be exploited and used by irresponsible parties in accessing something that is not their right. In addition to the computer security system that currently exists and is widely applied by various parties, of course this must also be balanced with awareness by its users in protecting existing resources, especially when related to personal data. Quishing is a type of phishing attack that utilizes QR (Quick Response) codes to trick users into accessing fake websites or downloading malware. Quishing is a development of traditional phishing attacks that use links or emails as a medium of fraud. In the case of quishing, users are asked to scan a QR code that appears legitimate, but turns out to lead to a site that has been manipulated by the attacker. The Nafidatunnajah Islamic Boarding School is one of the integrated Islamic education where the students are early childhood or adolescents, who certainly know or understand how to access the internet and use digital devices. However, the students have not been equipped with knowledge related to awareness in maintaining the security of personal data in cyberspace. In this case, we intend to conduct socialization related to Quishing at the Nafidatunnajah Islamic Boarding School as a form of introduction with the hope of increasing awareness in using the internet and digital devices, especially those related to data or resources that are personal in nature so as to avoid various threats of misuse by irresponsible people.